2021
DOI: 10.1002/ppul.25417
|View full text |Cite
|
Sign up to set email alerts
|

Central airway issues in bronchopulmonary dysplasia

Abstract: While there is a very large focus on the abnormalities of parenchymal lung development and extensive efforts to minimize alveolar damage with “gentle ventilation” and noninvasive respiratory support for neonates with bronchopulmonary dysplasia (BPD), there is relatively little consideration for the implications of central airway disease in this patient population. There are significant changes in the structure and conformation of the central airway during the last half of gestation, and premature birth disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 86 publications
0
16
1
Order By: Relevance
“…Failure of extubation or weaning respiratory support in patients with sBPD due to pathologies involving AE tract have been well reported in the literature. 23,[27][28][29] In our study, positive rate of 90.5% (38/42) was higher than rate of 74.0% (20/27) from previous study by Hysinger 4 in which only airway pathologies were identified. Utilizing the novel FE-NIV approach, we were safely take time and able to detailedly examined AE regions including pharyngolarynx, upper trachea and esophagus, and thus, yielded more pathologic findings.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Failure of extubation or weaning respiratory support in patients with sBPD due to pathologies involving AE tract have been well reported in the literature. 23,[27][28][29] In our study, positive rate of 90.5% (38/42) was higher than rate of 74.0% (20/27) from previous study by Hysinger 4 in which only airway pathologies were identified. Utilizing the novel FE-NIV approach, we were safely take time and able to detailedly examined AE regions including pharyngolarynx, upper trachea and esophagus, and thus, yielded more pathologic findings.…”
Section: Discussioncontrasting
confidence: 77%
“…These iatrogenic damages might result in tissue fibrosis, lumen stenosis and structural weakness. [21][22][23] In addition, infants with sBPD also encounter recurrent complications such as sepsis, cyanotic episodes, apnea and difficulty weaning. Therefore, they are best assessed and managed by a multidisciplinary team specializing in comprehensive care of the complex disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Since birth, they encounter frequent invasive trauma, such as intubations, suctions, infections, prolonged PPV, and systemic injuries of sepsis, hypoxia, and acidosis during their complicated and lengthy hospitalizations. These iatrogenic damages could result in AET tissue fibrosis, lumen narrowing, and structural weakness ( 23 25 ). Therefore, sBPD infants are best measured and managed by a multidisciplinary team that are specialized on comprehensive care of such diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comprehensive measurement with FE-NIV should be performed from the nostrils to the whole approachable bronchi, esophagus, and stomach. Lesions around the pharynx, larynx, subglottis, and tracheostomy can be assessed ( 23 27 ). Kurachek et al ( 28 ) reported that upper airway lesions like laryngomalacia, subglottic stenosis, etc., are the leading causes of extubation failure in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of early noninvasive ventilation strategies plays a crucial role in the context of pulmonary morbidity. 1,2 Recent multicentre studies and registry analyses indicate that further improvements in the management of noninvasive respiratory support are suited to improve the pulmonary outcome in the near term while novel therapeutic strategies still await a substantiated proof of benefit. 3,4 Enhanced energy and macronutrient intake during the first 4 weeks of life have been associated with improved somatic growth, neurodevelopmental outcomes, such as improved language scores and decreased incidence of brain lesions on magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%